ACADEMIC INTEGRITY IN EFL LEARNING: INSIGHTS FROM AN ISLAMIC HIGHER EDUCATION CONTEXT IN PEKANBARU - Jannah, Nurul; Miski, Cut Raudhatul (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This research aims to explore the forms of academic dishonesty and identify the factors that encourage academic dishonesty behavior among students majoring in English education at an Islamic university in Pekanbaru. This study uses a qualitative approach with a case study design. Participants in this study were sixth-semester students selected through purposive sampling techniques. In data collection, the researcher used closed questionnaires and interviews. The results of the study showed six main forms of academic dishonesty that are often carried out by EFL learning students, namely cheating on exams, plagiarism, outside help, prior cheating, falsification, and lying about academic assignments. These behaviors are driven by three main factors: academic pressure, opportunities to cheat, and rationalization of academic dishonesty. In conclusion, academic cheating behavior still occurs among EFL learner students with the most frequent form of academic dishonesty being falsification caused by several factors such as pressure, opportunity and rationalization. The findings are expected to raise student awareness and serve as a basis for lecturers and institutions to design prevention strategies. Future studies should focus on concrete solutions to prevent academic dishonesty in universities.